A rate-type electrolyte additive, electrolyte and lithium-ion battery

By using a symmetrical structure-containing methoxysilane group dimethyl ether compound as a magnification electrolyte additive in the lithium-ion battery electrolyte solution, combined with auxiliary additives, the insufficient performance of lithium-ion batteries in fast charging and discharge and cycle life is solved, and lower cell impedance and better battery charging and discharge performance are achieved.

CN119447472BActive Publication Date: 2025-03-21MONTA VISTA ENERGY TECH CORP (ANHUI)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510026087.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-21
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have insufficient performance in terms of fast charging and discharging and cycle life, especially in high-energy-density battery systems, the battery has a high interface impedance, which affects its charging and discharging performance and cycle life.

Method used

A methoxysilane group dimethyl ether compound containing a symmetric structure is used as a magnification electrolyte additive, combined with an auxiliary additive, to manufacture a lithium-ion battery electrolyte. This additive forms a stable interface film in the electrolyte, reducing the impedance of the positive and negative electrode interfaces and improving the transmission efficiency of lithium ions.

Benefits of technology

It significantly reduces the interface impedance of the positive and negative electrodes of lithium-ion batteries, improves the charging and discharging performance and cycle life of the battery, and also has excellent high-temperature storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447472B_ABST
    Figure CN119447472B_ABST
Patent Text Reader

Abstract

The present invention discloses a rate-type electrolyte additive, an electrolyte and a lithium-ion battery, which belong to the field of lithium-ion technology. The rate-type electrolyte additive is a dimethyl ether compound containing two symmetrically structured silane groups, and the general formula of the additive is:; The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and the above-mentioned rate-type electrolyte. The present invention uses a dimethyl ether compound of a symmetrically structured methoxysilane group as an additive to manufacture a lithium-ion battery electrolyte. The dimethyl ether compound containing a symmetrically structured methoxysilane group is used in combination with an auxiliary additive, and in a high-energy-density battery system, it has lower cell impedance, better battery charge-discharge and cycle performance, and can also take into account the high-temperature performance of the cell. The electrolyte is used to manufacture a lithium-ion battery, and the resulting battery has excellent charge-discharge performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ions, and in particular relates to a rate-type electrolyte additive, an electrolyte and a lithium ion battery. Background Art

[0002] Compared with other rechargeable batteries, lithium-ion batteries have the advantages of high energy density, high operating voltage, long cycle life and low self-discharge. At present, small-capacity lithium-ion batteries have been successfully used in electronic products such as mobile phones, digital cameras and laptops. At the same time, large-capacity and high-power lithium-ion power batteries also have good application prospects. In particular, the use of high-capacity positive and negative electrode materials and the improvement of the power transmission characteristics of the battery interface can effectively increase the battery energy density and high-rate charge and discharge capabilities. The realization of this technical goal depends largely on the electrolyte. The effect of the electrolyte on battery performance is mainly reflected in three aspects: the ionic conductivity of the electrolyte, the desolvation of lithium ions from the electrolyte, and the ion diffusion of the solid electrolyte film generated on the surface of the negative electrode. Modifying the interface chemical composition and properties of the electrode through electrolyte additives is a simple and efficient means. The design and optimization of electrolyte additives can not only improve the cycle life of the battery, but also improve the high-rate charge and discharge performance of the battery. More importantly, the development and use of multifunctional additives can reduce the use of other functional additives, and further reduce the cost of electrolytes and batteries while taking into account performance.

[0003] Therefore, based on the above considerations, it is necessary to develop a multifunctional additive and an electrolyte containing the additive, which can reduce the interfacial impedance of the battery itself while taking into account the performance of the battery in fast charging and discharging and cycle life. Summary of the invention

[0004] The object of the present invention is to provide a rate-type electrolyte additive, an electrolyte and a lithium-ion battery, so as to improve the fast charge and discharge performance and cycle life of the lithium-ion battery.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In the first aspect, the present application proposes a rate-type electrolyte additive, wherein the rate-type electrolyte additive is a dimethyl ether compound containing a silane group with two symmetrical structures, and the general formula of the rate-type electrolyte additive is as follows:

[0007] Formula 1;

[0008] In Formula 1, R 1 , R 2 , R 3 Each independently includes any one of hydrogen, fluorine, an alkyl group, an alkoxy group, a vinyl group and an amide group.

[0009] As further preferred, the rate-type electrolyte additive is at least one of compound 1, compound 2, compound 3 and compound 4;

[0010] The structure of compound 1 is shown below:

[0011] ;

[0012] The structure of compound 2 is shown below:

[0013] ;

[0014] The structure of compound 3 is shown below:

[0015] ;

[0016] The structure of compound 4 is shown below:

[0017] .

[0018] In the second aspect, the present application proposes a rate-type electrolyte, comprising the above-mentioned rate-type electrolyte additive, a non-aqueous organic solvent, a lithium salt and an auxiliary additive; the mass fraction of the rate-type electrolyte additive in the electrolyte is 0.1%~5%.

[0019] As a further preferred embodiment, the mass ratio of lithium salt in the electrolyte is 14.8%;

[0020] The mass ratio of the auxiliary additive in the electrolyte is 0.15% to 7.5%;

[0021] The balance is non-aqueous organic solvent.

[0022] As further preferred, the non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, γ-butyrolactone, γ-valerolactone, 1,3-dioxolane, 1,4-dioxane, propyl acetate, n-butyl acetate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether and their fluorides.

[0023] As a further preferred embodiment, the lithium salt is selected from LiPF 6 、LiAsF 6 、LiPO 2 F 2 、LiClO 4 , LiBF 4 , LiBOB, LiDFOB, LiFSI, LiTFSI, LiCH 3 SO 3、LiSbF 6 、LiCF 3 SO 3 、LiC(SO 2 CF 3 ) 3 、LiN(SO 2 C 2 F 5 ) 2 , lithium bis(fluorobis(oxaloyl)phosphate and lithium imide.

[0024] As further preferred, the auxiliary additive includes at least one of cyclic sulfate compounds, cyclic carbonate compounds, phosphate compounds, and borate compounds;

[0025] The cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate, and methyl vinyl sulfate;

[0026] The cyclic carbonate compound is at least one selected from vinylene carbonate, ethylene carbonate, methylene carbonate, fluoropropylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, and bisfluoroethylene carbonate;

[0027] The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphite;

[0028] The borate compound is selected from at least one of tris(triethylsilane)borate and tris(trimethylsilane)borate.

[0029] In the third aspect, the present application proposes a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an isolation membrane and the above-mentioned rate-type electrolyte; the positive electrode sheet comprises a positive electrode collector, a positive electrode active material, a conductive agent and a binder; the negative electrode sheet comprises a negative electrode collector, a negative electrode active material, a conductive agent and a binder.

[0030] As a further preferred embodiment, the material of the positive electrode current collector includes at least aluminum, and the positive electrode active material is selected from lithium transition metal oxides, including at least LiMO 2 (M=Ni,Co,Mn)、LiMn 2 O 4 、LiMPO 4 (M=Fe,Mn,Co), LiNi x Co y M 1-x-y O 2 (0≤x, y≤1 and x+y≤1; M=one or a mixture of Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Zn, Ga, Y, Zr, Nb, Mo, Sn, Ba or rare earth elements);

[0031] As a further preference, the negative electrode current collector is made of at least one of copper, stainless steel, aluminum, nickel, titanium, and carbon cloth;

[0032] The negative electrode active material is selected from graphite, mesophase carbon microspheres, Si, SiO x (0<x<2), one or a mixture of silicon-carbon material, lithium titanate, lithium metal, and lithium alloy.

[0033] Beneficial effects of the present invention:

[0034] The present invention uses a dimethyl ether compound of a symmetrically structured methoxysilane group as a rate-type electrolyte additive to manufacture a lithium-ion battery electrolyte. The dimethyl ether compound containing a symmetrically structured methoxysilane group is used in combination with an auxiliary additive, and in a high-energy-density battery system, it has a lower cell impedance, better battery charge-discharge and cycle performance, and can also take into account the high-temperature performance of the battery. The symmetrically structured silane group and dimethyl ether structure in the rate-type electrolyte additive have a higher oxidation potential, preferentially form a film at the interface of the positive and negative electrodes, and construct a solid interface film; secondly, the low viscosity and high diffusion coefficient are conducive to the rapid transmission of lithium ions; thirdly, the alkoxy group combines with the silanol group to form a mesh-like stable and dense interface film on the surface of the negative electrode, inhibiting the occurrence of interface side reactions and improving the stability of the electrolyte. Therefore, in a high-energy-density battery system, the interface impedance of the positive and negative electrodes can be significantly reduced, the battery charge-discharge performance can be improved, and it also has a long cycle life and excellent high-temperature storage performance. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The preparation method of the electrolyte disclosed in the present invention has no special requirements, as long as the components of the electrolyte are mixed evenly, there is no special limitation on the order of adding the components and the mixing method. For example, the organic solvent can be mixed evenly first, then the lithium salt can be added and mixed evenly, and then the above-mentioned rate-type electrolyte additive and auxiliary additive can be added.

[0037] The addition ratios in the following examples and comparative examples are all percentages by mass of the electrolyte.

[0038] Example 1

[0039] Prepare electrolyte:

[0040] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound having a methoxysilane group (compound 1) and an auxiliary additive to obtain an electrolyte;

[0041] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of methoxysilane group (compound 1) accounted for 1.0% by mass of the electrolyte, and the auxiliary additives accounted for 2.5% by mass of the electrolyte;

[0042] The auxiliary additives include vinylene carbonate, vinyl sulfate and tris(trimethylsilyl)phosphite, wherein the mass percentage of vinylene carbonate in the electrolyte is 0.8%, the mass percentage of vinyl sulfate in the electrolyte is 1.5%, and the mass percentage of tris(trimethylsilyl)phosphite in the electrolyte is 0.2%.

[0043] Example 2

[0044] Prepare electrolyte:

[0045] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound (compound 2) and an auxiliary additive to obtain an electrolyte;

[0046] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounts for 0.8% by mass of the electrolyte, the dimethyl ether compound of methoxysilane group (compound 2) accounts for 1.0% by mass of the electrolyte, and the auxiliary additive accounts for 2.5% by mass of the electrolyte;

[0047] The auxiliary additives include vinylene carbonate, vinyl sulfate and tris(trimethylsilyl)phosphite, wherein the mass percentage of vinylene carbonate in the electrolyte is 0.8%, the mass percentage of vinyl sulfate in the electrolyte is 1.5%, and the mass percentage of tris(trimethylsilyl)phosphite in the electrolyte is 0.2%.

[0048] Example 3

[0049] Prepare electrolyte:

[0050] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound having a methoxysilane group (compound 3) and an auxiliary additive to obtain an electrolyte;

[0051] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of methoxysilane group (compound 3) accounted for 1.0% by mass of the electrolyte, and the auxiliary additives accounted for 2.5% by mass of the electrolyte;

[0052] The auxiliary additives include vinylene carbonate, vinyl sulfate and tri(trimethylsilyl)phosphite; the mass percentage of vinylene carbonate in the electrolyte is 0.8%, the mass percentage of vinyl sulfate in the electrolyte is 1.5%, and the mass percentage of tri(trimethylsilyl)phosphite in the electrolyte is 0.2%.

[0053] Example 4

[0054] Prepare electrolyte:

[0055] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound (compound 4) and an auxiliary additive to obtain an electrolyte;

[0056] Among them, LiPF 6The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of methoxysilane group (compound 4) accounted for 1.0% by mass of the electrolyte, and the auxiliary additives accounted for 2.5% by mass of the electrolyte;

[0057] The auxiliary additives include vinylene carbonate, vinyl sulfate and tris(trimethylsilyl)phosphite, wherein the mass percentage of vinylene carbonate in the electrolyte is 0.8%, the mass percentage of vinyl sulfate in the electrolyte is 1.5%, and the mass percentage of tris(trimethylsilyl)phosphite in the electrolyte is 0.2%.

[0058] Example 5

[0059] Prepare electrolyte:

[0060] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound of a methoxysilane group (compound 1), a dimethyl ether compound of a methoxysilane group (compound 2) and an auxiliary additive to obtain an electrolyte;

[0061] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 1) accounted for 0.2% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 2) accounted for 0.8% by mass of the electrolyte, and the auxiliary additives accounted for 4.2% by mass of the electrolyte;

[0062] The auxiliary additives include fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and tris(triethylsilane)borate, wherein the mass percentage of fluoroethylene carbonate in the electrolyte is 2%, the mass percentage of vinylene carbonate in the electrolyte is 1%, the mass percentage of vinyl sulfate in the electrolyte is 1%, and the mass percentage of tris(triethylsilane)borate in the electrolyte is 0.2%.

[0063] Example 6

[0064] Prepare electrolyte:

[0065] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound of a methoxysilane group (compound 3), a dimethyl ether compound of a methoxysilane group (compound 4) and an auxiliary additive to obtain an electrolyte;

[0066] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (compound 3) accounted for 0.2% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (compound 4) accounted for 0.8% by mass of the electrolyte, and the auxiliary additives accounted for 4.2% by mass of the electrolyte;

[0067] The auxiliary additives include fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and tris(triethylsilane)borate; the mass percentage of fluoroethylene carbonate in the electrolyte is 2%, the mass percentage of vinylene carbonate in the electrolyte is 1%, the mass percentage of vinyl sulfate in the electrolyte is 1%, and the mass percentage of tris(triethylsilane)borate in the electrolyte is 0.2%.

[0068] Example 7

[0069] Prepare electrolyte:

[0070] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound of a methoxysilane group (compound 1), a dimethyl ether compound of a methoxysilane group (compound 3) and an auxiliary additive to obtain an electrolyte;

[0071] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 1) accounted for 0.5% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 3) accounted for 0.5% by mass of the electrolyte, and the auxiliary additives accounted for 4.2% by mass of the electrolyte;

[0072] The auxiliary additives include fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and tris(triethylsilane)borate; the mass percentage of fluoroethylene carbonate in the electrolyte is 2%, the mass percentage of vinylene carbonate in the electrolyte is 1%, the mass percentage of vinyl sulfate in the electrolyte is 1%, and the mass percentage of tris(triethylsilane)borate in the electrolyte is 0.2%.

[0073] Example 8

[0074] Prepare electrolyte:

[0075] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), a dimethyl ether compound of a methoxysilane group (compound 2), a dimethyl ether compound of a methoxysilane group (compound 4) and an auxiliary additive to obtain an electrolyte;

[0076] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 2) accounted for 0.5% by mass of the electrolyte, the dimethyl ether compound of the methoxysilane group (Compound 4) accounted for 0.5% by mass of the electrolyte, and the auxiliary additives accounted for 4.2% by mass of the electrolyte;

[0077] The auxiliary additives include fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and tris(triethylsilane)borate; the mass percentage of fluoroethylene carbonate in the electrolyte is 2%, the mass percentage of vinylene carbonate in the electrolyte is 1%, the mass percentage of vinyl sulfate in the electrolyte is 1%, and the mass percentage of tris(triethylsilane)borate in the electrolyte is 0.2%.

[0078] Comparative Example 1

[0079] Prepare electrolyte:

[0080] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), vinylene carbonate, vinyl sulfate and tris(trimethylsilyl)phosphite to obtain the electrolyte of this comparative example;

[0081] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounts for 0.8% by mass of the electrolyte, vinylene carbonate accounts for 0.8% by mass of the electrolyte, vinyl sulfate accounts for 1.5% by mass of the electrolyte, and tris(trimethylsilyl)phosphite accounts for 1% by mass of the electrolyte.

[0082] Comparative Example 2

[0083] Prepare electrolyte:

[0084] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), vinylene carbonate, vinyl sulfate and tris(triethylsilane)borate to obtain the electrolyte of this comparative example;

[0085] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounts for 0.8% by mass of the electrolyte, vinylene carbonate accounts for 0.8% by mass of the electrolyte, vinyl sulfate accounts for 1.5% by mass of the electrolyte, and tris(triethylsilyl)borate accounts for 1% by mass of the electrolyte.

[0086] Comparative Example 3

[0087] Prepare electrolyte:

[0088] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, tris(triethylsilane)borate, to obtain the electrolyte of this comparative example;

[0089] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounted for 0.8% by mass of the electrolyte, fluoroethylene carbonate accounted for 2% by mass of the electrolyte, vinylene carbonate accounted for 1% by mass of the electrolyte, vinyl sulfate accounted for 1% by mass of the electrolyte, and tris(triethylsilyl)borate accounted for 1% by mass of the electrolyte.

[0090] Comparative Example 4

[0091] Prepare electrolyte:

[0092] In an argon glove box, ethylene carbonate, propyl propionate and ethyl propionate were mixed in a weight ratio of 30:20:50 to obtain a non-aqueous organic solvent, and LiPF was added to the non-aqueous organic solvent. 6 , lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO 2 F 2 ), fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, tris(trimethylsilyl)phosphite, to obtain the electrolyte of this comparative example;

[0093] Among them, LiPF 6 The mass percentage of the electrolyte is 11%, the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 3%, and the mass percentage of lithium difluorophosphate (LiPO 2 F 2 ) accounts for 0.8% by mass of the electrolyte, fluoroethylene carbonate accounts for 2% by mass of the electrolyte, vinylene carbonate accounts for 1% by mass of the electrolyte, vinyl sulfate accounts for 1% by mass of the electrolyte, and tris(trimethylsilyl)phosphite accounts for 1%.

[0094] The electrolyte parameter table corresponding to Example 1 to Example 8 and Comparative Example 1 to Comparative Example 4 is shown in Table 1:

[0095] Table 1

[0096]

[0097] Preparation of positive electrode sheet: The ternary positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 , conductive agent CNT (carbon nanotube), binder PVDF (polyvinylidene fluoride) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.

[0098] Preparation of negative electrode sheet: The negative electrode active material silicon oxygen-carbon composite material, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0099] Production of lithium-ion batteries: PE porous polymer film is used as a separator. The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then the stacked electrode sheet and separator are wound to obtain a roll core. The roll core is placed in the aluminum-plastic film bag that has been punched and formed, and the electrolyte prepared above is injected into the baked and dried battery cells. After vacuum packaging, standing, formation and other processes, the preparation of lithium-ion batteries is completed.

[0100] Performance Testing

[0101] The lithium ion batteries prepared in the above Examples 1-8 and Comparative Examples 1-4 were subjected to the following performance tests.

[0102] 25℃ DCIR performance test:

[0103] At 25°C, the battery was first charged to 4.2V with 0.5C constant current and constant voltage, then charged at 4.2V constant voltage, with a cut-off current of 0.005C, and then discharged to 2.65V with 0.5C constant current, for 2 pre-cycles. Then, it was charged to 50% of the charging capacity with 0.5C constant current and constant voltage, left at 25°C for 3 hours, and then charged and discharged for 10 seconds at 0.1C, 0.2C, and 0.5C, respectively, and left for 40 seconds, and the 25°C DCIR internal resistance was calculated.

[0104] The test results are shown in Table 2 below:

[0105] Table 2

[0106]

[0107] The results of Comparative Example 1, Comparative Example 2, and Examples 1 to 4 in Table 2 show that the 25°C DCIR performance test has been significantly improved. This is mainly due to the protective effect of the film-forming of the rate-type electrolyte additive on the positive and negative electrode interfaces. The interfacial film is almost not dissolved, the interface is relatively stable, and the combination of lithium ion transmission is promoted. Compound 1 selected from the rate-type electrolyte additive in Example 1 has a symmetrical molecular structure. At the same time, the fluorine element at the end group has a strong electronegativity and good antioxidant properties, which is conducive to reduction and film formation on the negative electrode surface. In Example 2, Compound 2 in the rate-type electrolyte additive is selected, and the alkoxysilane reacts with the silanol group to form a Si—O—Si network, thereby stabilizing the charged interface and improving the electrochemical performance. In Example 3, Compound 3 selected from the rate-type electrolyte additive introduces an unsaturated bond at the end group, and the carbon-carbon double bond is bonded to other atoms in the form of SP2 and SP hybridization, which has a conjugated effect and can induce PF 5 Corrosive acids such as alkoxysilane and alkoxysilane can form bonds with compounds containing lone pairs of electrons, so the unsaturated alkoxysilane group contained in compound 3 has a strong ability to capture PF 5 The ability of corrosive acids to inhibit LiPF 6 The hydrolysis of the electrolyte is further stabilized to improve the cycle performance of the battery. In Example 4, the compound 4 selected from the rate-type electrolyte additive, the presence of the unsaturated functional group and the amide group enables the compound 4 to be reduced on the surface of the Si negative electrode and form an effective SEI film. The nitrogen-containing compound formed in the SEI film has a high ionic conductivity to reduce the polarization phenomenon of the battery, thereby improving the cycle performance of the battery.

[0108] From Comparative Example 3, Comparative Example 4, and Examples 6 to 8 in Table 2, it can be seen that after adjusting the combination of auxiliary additives, the various performances of the lithium-ion battery are improved to a certain extent by adding the compound of the combined additive. In Example 7, the interfacial impedance of the battery is reduced and the battery cycle performance is improved through the synergistic effect of the auxiliary additives and the compound 1 and compound 3 in the rate-type electrolyte additive. This shows that the combination of additives can form a film on the surface of the positive and negative electrodes to inhibit the side reactions at the interface, and can also be combined with oxygen release to inhibit the oxidation and gas production of the electrolyte by oxygen release, which can effectively stabilize the electrolyte.

[0109] From Example 1 to Example 8 in Table 2, the combination of different auxiliary additives, compounds 1 to 4 in the rate-type electrolyte additives, and different types and content combinations have different effects on improving the various performances of lithium-ion batteries. R&D personnel can use them reasonably according to the performance requirements of their own products.

[0110] The lithium ion battery electrolyte and the lithium ion battery of the present invention are described according to the embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. By reading the above description, many embodiments and many applications other than the examples provided will be obvious to those skilled in the art.

[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0112] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A rate-type electrolyte additive, characterized in that: The rate-type electrolyte additive is a dimethyl ether compound containing two symmetrically structured silane groups. The general formula of the rate-type electrolyte additive is as follows: Formula 1; In formula I, R1, R2, and R3 independently include any one of hydrogen, fluorine, alkyl, alkoxy, vinyl, and amide.

2. A rate-type electrolyte additive according to claim 1, characterized in that: The rate-type electrolyte additive is at least one of compound 1, compound 2, compound 3 and compound 4; The structure of compound 1 is shown below: ; The structure of compound 2 is shown below: ; The structure of compound 3 is shown below: ; The structure of compound 4 is shown below: 。 3. A rate-type electrolyte, characterized in that: It comprises a non-aqueous organic solvent, a lithium salt, an auxiliary additive and the rate-type electrolyte additive according to any one of claims 1 to 2; the mass fraction of the rate-type electrolyte additive in the electrolyte is 0.1% to 5%; the auxiliary additive comprises at least one of cyclic sulfate compounds, cyclic carbonate compounds, phosphate compounds and borate compounds.

4. A rate-type electrolyte according to claim 3, characterized in that: The mass ratio of lithium salt in the electrolyte is 14.8%; The mass ratio of the auxiliary additive in the electrolyte is 0.15% to 7.5%; The balance is non-aqueous organic solvent.

5. A rate-type electrolyte according to claim 3, characterized in that: The non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, γ-butyrolactone, γ-valerolactone, 1,3-dioxolane, 1,4-dioxane, propyl acetate, n-butyl acetate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether and their fluorides.

6. A rate-type electrolyte according to claim 3, characterized in that: The lithium salt is selected from at least one of LiPF6, LiAsF6, LiPO2F2, LiClO4, LiBF4, LiBOB, LiDFOB, LiFSI, LiTFSI, LiCH3SO3, LiSbF6, LiCF3SO3, LiC(SO2CF3)3, LiN(SO2C2F5)2, lithium bis(fluorobis(oxalyl)phosphate) and lithium imide.

7. A rate-type electrolyte according to claim 3, characterized in that: The cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate, and methyl vinyl sulfate; The cyclic carbonate compound is at least one selected from vinylene carbonate, ethylene carbonate, methylene carbonate, fluoropropylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, and bisfluoroethylene carbonate; The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphite; The borate compound is selected from at least one of tris(triethylsilane)borate and tris(trimethylsilane)borate.

8. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and the rate-type electrolyte described in any one of claims 3 to 7; the positive electrode sheet comprises a positive electrode collector, a positive electrode active material, a conductive agent and a binder; the negative electrode sheet comprises a negative electrode collector, a negative electrode active material, a conductive agent and a binder.

9. A lithium ion battery according to claim 8, characterized in that: The material of the positive electrode current collector includes aluminum; The positive electrode active material is selected from lithium transition metal oxides LiMO2, LiMn2O4, transition metal oxides LiMPO4 and transition metal oxides LiNi x Co y M 1-x-y One of O2; In the transition metal oxide LiMO2, M is selected from at least one of Ni, Co, and Mn; In the transition metal oxide LiMPO4, M is selected from at least one of Fe, Mn and Co; Transition Metal Oxide LiNi x Co y M 1-x-y In O2, 0≤x, y≤1 and x+y≤1; M is selected from at least one of Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Zn, Ga, Y, Zr, Nb, Mo, Sn, Ba and rare earth elements.

10. A lithium ion battery according to claim 9, characterized in that: The negative electrode current collector is made of at least one of copper, stainless steel, aluminum, nickel, titanium, and carbon cloth; The negative electrode active material is selected from graphite, mesophase carbon microspheres, Si, silicon-carbon materials, lithium titanate, lithium metal, lithium alloy, SiO x At least one of; wherein, 0<x<2.

Citation Information

Patent Citations

  • Nonaqueous electrolytic solution and secondary battery using the same

    JP2004171981A

  • Electrolyte solution and secondary battery

    WO2018028392A1